2014
DOI: 10.1002/xrs.2544
|View full text |Cite
|
Sign up to set email alerts
|

Optimized energy dispersive X-ray fluorescence analysis of atmospheric aerosols collected at pristine and perturbed Amazon Basin sites

Abstract: Elemental composition of aerosols is important to source apportionment studies and to understand atmospheric processes that influence aerosol composition. Energy dispersive X‐ray fluorescence spectroscopy was applied for measuring the elemental composition of Amazonian atmospheric aerosols. The instrument used was a spectrometer Epsilon 5, PANalytical B.V., with tridimensional geometry that reduces the background signal with a polarized X‐ray detection. The measurement conditions were optimized for low‐Z eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
1
17
0
2
Order By: Relevance
“…From polarization Raman lidar measurements in Cyprus it was, for example, concluded that mineral dust contributes 10–50% to the optical extinction of smoke plumes, corresponding to a contribution between 25 and 80% to the aerosol mass [ Nisantzi et al , ]. Measurements of the dust fraction in lofted Amazonian biomass burning plumes were not reported yet, but surface in situ observations in the Amazon Basin analyzed by Arana et al [] suggest that the dust fraction is lower in that region than over Cyprus. For both the dry and wet season, observations in the vicinity of biomass burning activity yield a soil dust fraction of approximately 4% of the total particulate mass and a fraction between soil dust and black carbon of 50–60%.…”
Section: Resultsmentioning
confidence: 99%
“…From polarization Raman lidar measurements in Cyprus it was, for example, concluded that mineral dust contributes 10–50% to the optical extinction of smoke plumes, corresponding to a contribution between 25 and 80% to the aerosol mass [ Nisantzi et al , ]. Measurements of the dust fraction in lofted Amazonian biomass burning plumes were not reported yet, but surface in situ observations in the Amazon Basin analyzed by Arana et al [] suggest that the dust fraction is lower in that region than over Cyprus. For both the dry and wet season, observations in the vicinity of biomass burning activity yield a soil dust fraction of approximately 4% of the total particulate mass and a fraction between soil dust and black carbon of 50–60%.…”
Section: Resultsmentioning
confidence: 99%
“…Since the late 1980s, numerous field campaigns have been conducted in the Amazon region, which focused on specific aspects of the complex atmospheric cycling for time periods of weeks, months, and in some cases up to years (e.g., Andreae et al, 1988Andreae et al, , 2004Andreae et al, , 2015Talbot et al, 1988Talbot et al, , 1990Harriss et al, 1990;Artaxo et al, 1993Artaxo et al, , 2013bMartin et al, 2010aBrito et al, 2014;Wendisch et al, 2016). In 2010/11, the Amazon tall tower observatory (ATTO) has been established ∼ 150 km northeast (NE) of the city of Manaus, Brazil, for continuous and detailed observation of meteorology, trace gases, aerosols, and ecology in order to study long-term trends of the Amazonian hydrological and biogeochemical cycling in relation to the increasing extent of manmade perturbations (Andreae et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Energy dispersive x-ray fluorescence (EDXRF) analysis was used to quantify elements with atomic numbers ≥11 (Na and heavier) on the filters (Arana et al, 2014). The elements sodium (Na), magnesium 30 (Mg), aluminum (Al), silicon (Si), phosphorus (P), sulfur (S), chlorine (Cl), potassium (K), calcium (Ca), titanium (Ti), manganese (Mn), and iron (Fe) have been analyzed in detail in the context of this study.…”
mentioning
confidence: 99%
“…The elements sodium (Na), magnesium 30 (Mg), aluminum (Al), silicon (Si), phosphorus (P), sulfur (S), chlorine (Cl), potassium (K), calcium (Ca), titanium (Ti), manganese (Mn), and iron (Fe) have been analyzed in detail in the context of this study. The detection limits for the individual elements are shown in Table S2, based on the work by Arana et al (2014). (Fig.…”
mentioning
confidence: 99%